1996
DOI: 10.1115/1.2792691
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Method for Power Plant Simulations

Abstract: This paper describes a highly flexible computerized method of calculating operating data in a power cycle. The computerized method presented here permits the study of steam, gas and combined plants, Its flexibility is not restricted by any defined cycle scheme. A power plant consists of simple elements (turbine, compressor, combustor chamber, pump, etc.). Each power plant componment is represented by its typical equations relating to fundamental mechanical and thermodynamic laws, so a power plant system is rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 6 publications
0
25
0
Order By: Relevance
“…In this study we present the development of the required tools for simulation of CRGT plants, based on the modular approach developed by Carcasci and Facchini [5]. The current paper is restricted to development of tools for thermodynamic analysis of CRGT cycles.…”
Section: Modular Approach For Thermodynamic Analysis Of Crgt Power Plmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study we present the development of the required tools for simulation of CRGT plants, based on the modular approach developed by Carcasci and Facchini [5]. The current paper is restricted to development of tools for thermodynamic analysis of CRGT cycles.…”
Section: Modular Approach For Thermodynamic Analysis Of Crgt Power Plmentioning
confidence: 99%
“…A complete presentation of the modular approach used by the authors for power plant simulation may be found in a previous paper [5]. The method is summarized below.…”
Section: Modular Approach For Thermodynamic Analysis Of Crgt Power Plmentioning
confidence: 99%
“…For an assigned fuel/air ratio of the burner, the mass flow rate of hot gas produced by the burner is proportional to the consumed fuel. To optimize computational resources for a Real Time application, authors preferred a tabular approach: a model developed by Carcasci [28], for the performance analysis in steady state conditions, is used to determine temperatures and exchanged heat fluxes of the plant considering different off-design conditions. These simulations are performed off-line.…”
Section: Detailed Model Of the Steam Generatormentioning
confidence: 99%
“…The calculation of the outlet temperatures of superheater T SH and reheater T RH are approximated using tabulated results from static off-line simulations of the plant in off-design conditions. Off-line simulations are performed with a model previously developed by Carcasci [28].…”
Section: Detailed Model Of the Steam Generatormentioning
confidence: 99%
See 1 more Smart Citation